8 jonge kunstenaars. - Galerie Nouvelles Images, Den Haag (Den Haag : Galerie Nouvelles Images, 1990)
Ang, Tiong, Baumann, Dagmar ; Neutkens, Harjo ; Kuijer, Ruud ; Paardenkooper, Majella ; Schouten, Hella ; Slagmolen, Ludo ; De Zeeuw, Marjam
8 jonge kunstenaars, Galerie Nouvelles Images, Den Haag, 21 januari - 14 februari 1990
boek